2022
DOI: 10.1002/advs.202200717
|View full text |Cite
|
Sign up to set email alerts
|

Functional Phosphoproteomics in Cancer Chemoresistance Using CRISPR‐Mediated Base Editors

Abstract: Selective inhibition of targeted protein kinases is an effective therapeutic approach for treatment of human malignancies, which interferes phosphorylation of cellular substrates. However, a drug-imposed selection creates pressures for tumor cells to acquire chemoresistance-conferring mutations or activating alternative pathways, which can bypass the inhibitory effects of kinase inhibitors. Thus, identifying downstream phospho-substrates conferring drug resistance is of great importance for developing poly-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…We next examined whether mutation of phosphosites important for cell division would affect cell viability or proliferation in our pooled format without specific stimuli or selective pressure 37 . Examination of phosphorylation sites on CDK1, a kinase whose activity is necessary for proper cell division, showed that Y160C;T161A and Y15C reduced cell viability post-ABE8e electroporation similar in magnitude and direction to levels previously seen using homology-directed recombination 38 ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next examined whether mutation of phosphosites important for cell division would affect cell viability or proliferation in our pooled format without specific stimuli or selective pressure 37 . Examination of phosphorylation sites on CDK1, a kinase whose activity is necessary for proper cell division, showed that Y160C;T161A and Y15C reduced cell viability post-ABE8e electroporation similar in magnitude and direction to levels previously seen using homology-directed recombination 38 ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Our study focused on phosphosites empirically identified in a parallel experiment rather than from PTM repositories or databases, mitigating the introduction of indiscriminate coding mutations that can have PTM-independent effects 20,21,37 . Moreover, as phosphoproteomic analyses of novel, unstudied systems continue to grow (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed the discovery of essential mediators of sensitivity or resistance to IFN-γ, and, importantly, a strong overlap with available patient data was observed [112]. In another study, CRISPR-mediated screens with CBEs and ABEs targeting altogether nearly 18,000 phosphorylation sites were performed in the CRC HCT116 cells to understand resistance mechanisms to the anti-metabolite 5-fluorouracil, thus leading to the identification of RSK2 and PAK4 kinase substrates [113].…”
Section: Crispr-based Base-editing Screensmentioning
confidence: 99%
“…[ 7,10 ] To expand their targeting scope, elevate their targeting efficiencies, and minimize their off‐targeting activities, various base editor derivates have been developed by replacing or engineering novel deaminases. [ 11‐14 ] Since then, base editors have been widely used for annotating the functional significance of SNVs or modifications in a low‐ or high‐throughput manner, [ 15‐19 ] as we have reported previously. Considering the restriction of protospacer adjacent motif (PAM) sequences and protein sizes for distinct Cas9 proteins, Cas9 is engineered or replaced by other orthologs or other Cas proteins to expand the versatility and efficiency of in vitro and in vivo genome editing.…”
Section: Introductionmentioning
confidence: 99%